User Interface dan User Experience Learning Management System Universitas Negeri Padang Berbasis Aplikasi Mobile - M. Iqbal Has; Eko Purnomo (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
Learning Management System is a software platform designed to support and manage online teaching and learning activities. One of the educational institutions that have used the LMS platform is Padang State University. The UNP LMS platform itself has been released since 2019 which is called E-Learning UNP. At that time its use was fairly rare because it was still in the development period. However, the use of the UNP LMS platform has problems with its user interface and user experience which causes online teaching and learning activities to be less effective. The unrest felt is the usability of the UNP LMS platform which still cannot meet user needs efficiently and effectively. The design of the Padang State University mobile learning management system application uses the Design Thimgking method, so it can be concluded that this design is a problem sourced from empathy, the need for a solution to an existing problem, then continue to test for improvement. Then the mobile learning management system application was created as the main media, and accompanied by other supporting media such as Motion Graphic, Poster, X-Banner, Sticker, Acrylic Stand, and High Fidelity Flow.